2012
DOI: 10.1177/1077546312464260
|View full text |Cite
|
Sign up to set email alerts
|

Performance of earth-moving machinery cab with hydraulic mounts in low frequency

Abstract: The purpose of this study is to explore the low-frequency advantages and characteristics of the hydraulic mounts used for vibration isolation of an earth-moving machinery cab. For the feature of the cab’s center of mass being relatively high above the cab’s supporting surface, the pitch and roll vibrations of the cab are prone to generate in the low frequency range. A six-degree-of-freedom (d.f.) model of the cab supported by hydraulic mounts with quadratic damping is set up in this paper. And the simulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The reference parameters of the vehicle are given in Table 2. In addition, for the lumped parameters of three cab's isolation mounts, as listed in Table 3, herein, the traditional rubber mounts and the main rubber of hydraulic mounts are the same stiffness and damping constants [21]. The static stiffness constants of pneumatic mounts are also equivalently calculated with the above two isolation mounts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference parameters of the vehicle are given in Table 2. In addition, for the lumped parameters of three cab's isolation mounts, as listed in Table 3, herein, the traditional rubber mounts and the main rubber of hydraulic mounts are the same stiffness and damping constants [21]. The static stiffness constants of pneumatic mounts are also equivalently calculated with the above two isolation mounts.…”
Section: Resultsmentioning
confidence: 99%
“…A six-degreeof-freedom (DOF) cab model of earth-moving machinery with the hydraulic mounts involving quadratic damping was also investigated under the road roughness excitation within a frequency range below 10 Hz [21]. The results showed that the root mean square (RMS) of acceleration responses and the power spectral density (PSD) of displacement responses of the cab's mass centre are all reduced remarkably with the comparison between hydraulic and rubber mounts.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Then, they analyzed the effect of the device active suspended cab on the human body vibration and did the study of the operators' comfort [1]. Aiming at improving operating conditions, Sun and Zhang had done the low-frequency vibration study of the bulldozer cab vibration; then, the structure design and improvement scheme of the equipment had been proposed [2]. Xu et al had established a comprehensive model of a cab and an operator; then, the damping layout way had been researched [3].…”
Section: Introductionmentioning
confidence: 99%
“…And the simulation which compares performance of the hydraulic mounts and the rubber mounts used in the cab is carried out. It shows that the cab system with quadratic damping hydraulic mounts has remarkable efficiency to mitigate the vibrations and in turn to enhance the cab comfort [2]. The ride dynamics of typical North-American soil compactors were investigated via analytical and experimental methods.…”
Section: Introductionmentioning
confidence: 99%